Pattern of Pesticide and Herbicide Poisoning Among People Admitted to Medicine Wards of a Tertiary Care Hospital (Medicine Today, 2024)
Introduction: Acute poisoning has become a major public health problem accounting for significant morbidity and mortality around the globe2. According to WHO data, an estimated 193,460 people died worldwide in 2012 from unintentional acute poisoning. 84% of these deaths occurred in resource-lacking low- and middle income countries3. The toxicity of accessible poisons and the scarcity of adequate medical facilities for poisoning management is responsible for a such a high mortality rate in this region4. Acute pesticide poisoning usually occurs during agricultural use either by accidental exposure or by suicidal attempt, rarely as homicidal2,5&8. This study is designed to assess the patterns of pesticide & herbicide poisoning among rural & urban peoples admitted to medicine ward of a tertiary level hospital and to find out the sociodemographic characteristics of the respondents. So that the supply of these agents be properly regulated to prevent easy accessibility and misuse. Materials and Methods: It was a hospital based cross-sectional observational study conducted at indoor Department of Medicine, Chittagong Medical College Hospital for six months period from 01/01/2019 to 31/06/2019. Ethical clearance was taken from ethical review committee of Chittagong Medical College and informed consent was obtained from each participants. Hundred patients above 12 years of age with a relevant history and clinical signs and symptoms of any type of pesticides and herbicides poisoning who fulfilled the selection criteria were selected consecutively for the study. Data was collected using a pretested, multi-structured questionnaire which comprised of questions to identify demographic data, type and circumstances of poisoning. Results: Regarding motive of poisoning in our study 81% patient took pesticide & herbicide poisoning for suicide and 19% admitted with accidental case. This result is consistent with the study where most common reason of pesticide & herbicide poisoning was suicide (93.3%) 20. A study performed at Rajshahi Medical College from January 1991 to December 1994 showed that out of those 405 cases of OPC poisoning 310 were suicidal (76.54%) and 95 were homicidal (23.45%) poisoning28. The present study revealed that factors responsible for the suicidal attempt were familial disharmony in 46% of cases, marital problems in 19%, financial problem in 16%, mental disorder in 3% and 11% due to other reasons. Shadequl-Islam et al. reported the motive of pesticide poisoning in their study that 45% of cases were due to familial disharmony, 15% unknown, 13.3% depression, 8.3% marital problems, 5% financial problems and 13.3% due to other reasons26. In most cases, the patient could access to the poison by self-purchasing from poison retailers. Conclusion: This study has indicated that young adults, males and socially underprivileged people are at a higher risk of pesticides and herbicides poisoning. This study showed pesticides & herbicides poisoning is the most common modes of suicidal deaths. Pesticides are mostly misused purposefully as an easy means for committing suicide. Early diagnosis and treatment is mandatory in order to minimize mortality from these potentially lethal compounds. It is recommended that the supply of pesticides be properly regulated to prevent easy accessibility and misuse.Medicine Today 2023 Vol.36 (1): 36-40